2016
DOI: 10.1016/j.scitotenv.2016.05.132
|View full text |Cite
|
Sign up to set email alerts
|

Sorption, photodegradation, and chemical transformation of naproxen and ibuprofen in soils and water

Abstract: Pharmaceutically active compounds (PhACs) are released into the environment where they undergo soil sorption, photodegradation, and chemical transformation into structurally similar compounds. Here we report on studies of naproxen (NAP) and ibuprofen (IBP), two widely-used nonsteroidal anti-inflammatory drugs (NSAIDS), in soils and water. Organic matter (OM) was observed to play an important role in each of these processes. Sorption was observed to be stronger and nonlinear in higher OM soils while weaker but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 58 publications
(75 reference statements)
1
24
0
6
Order By: Relevance
“…However, for NAP-PT2, SRFA and SRHA had a negligible effect at 10 mg/L (SRFA t 1/2 = 15 h, SRHA t 1/2 = 15 h) but a more noticeable effect at 25 mg/L (SRFA t 1/2 = 26 h, SRHA t 1/2 = 20 h). Compared to the half-life of naproxen (t 1/2 = 0.7 h [5 μg/L, pH 7.0]; Vulava et al 2016), the observed phototransformation half-lives, across these conditions, were approximately 20 times longer for NAP-PT1 and 20 to 40 times longer for NAP-PT2.…”
Section: Photochemistry Of Naproxen and Its Phototransformation Productsmentioning
confidence: 88%
“…However, for NAP-PT2, SRFA and SRHA had a negligible effect at 10 mg/L (SRFA t 1/2 = 15 h, SRHA t 1/2 = 15 h) but a more noticeable effect at 25 mg/L (SRFA t 1/2 = 26 h, SRHA t 1/2 = 20 h). Compared to the half-life of naproxen (t 1/2 = 0.7 h [5 μg/L, pH 7.0]; Vulava et al 2016), the observed phototransformation half-lives, across these conditions, were approximately 20 times longer for NAP-PT1 and 20 to 40 times longer for NAP-PT2.…”
Section: Photochemistry Of Naproxen and Its Phototransformation Productsmentioning
confidence: 88%
“…The concentration of naproxen in the environment depends on its physicochemical properties such as solubility and chemical stability as well as environmental properties, while its mobility in the environment correlates to chemical properties such as the dissociation constant and the value of the octanolwater partition coefficient (logK ow ) (Kim and Zoh 2016;Sibeko et al 2019). The value of this coefficient for naproxen (3.2) indicates that this compound is hydrophobic (Vulava et al 2016).…”
Section: Occurrence Of Naproxen In the Environmentmentioning
confidence: 99%
“…This stock solution was diluted to obtain solutions at five initial concentrations of ibuprofen (~1.0, 5.0, 10.0, 15.0, and 20.0 mg/l). Initial ibuprofen concentrations for sorption experiments in this study fall within the concentration range commonly applied in other studies (Estevez et al 2014;Vulava et al 2016).…”
Section: Methodsmentioning
confidence: 68%
“…The stock solution of ibuprofen (~20.0 mg/l) was prepared in 0.01 mol/l CaCl 2 and 100 mg/l NaN 3 aqueous solution. Sodium azide was used to prevent microbial degradation of ibuprofen in sorption-desorption experiments of this study although Vulava et al (2016) demonstrated that ibuprofen was not degraded during a 7-day sorption experiment. This stock solution was diluted to obtain solutions at five initial concentrations of ibuprofen (~1.0, 5.0, 10.0, 15.0, and 20.0 mg/l).…”
Section: Methodsmentioning
confidence: 96%